Kuat Tekan Dan Ultasonic Pulse Velocity (UPV) Beton OPC Dan OPC Abu Sekam Padi Untuk Aplikasi Di Lingkungan Gambut - Muhammad Farhan Setyawan; Iskandar Romey Sitompul; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research study the compressive strength and ultrasonic pulse velocity (UPV) of OPC and OPC rice husk ash (RHA) concrete. Test will be measured after 28 days immersed in peat water. Specimens will be immersed in peat water after 28 days cured in normal water. Compressive strength of OPC concrete showed biggest value than OPC with admixture RHA 5% and 10% which is increasing amount of RHA for subsitute cement will decreasing compressive strength. Test UPV of the specimen showed OPC RHA 5% being best quality than other.Keywords: Durabilty, OPC, RHA, peat environment.